Annealing Study on Praseodymium-Doped Indium Zinc Oxide Thin-Film Transistors and Fabrication of Flexible Devices - Zhenyu Wu; Honglong Ning; Han Li; Xiaoqin Wei; Dongxiang Luo; Dong Yuan; Zhihao Liang; Guoping Su; Rihui Yao; Junbiao Peng (Micromachines)
The praseodymium-doped indium zinc oxide (PrIZO) thin-film transistor (TFT) is promising for applications in flat-panel displays, due to its high carrier mobility and stability. Nevertheless, there are few studies on the mechanism of annealing on PrIZO films and the fabrication of flexible devices. In this work, we first optimized the annealing-process parameters on the glass substrate. As the annealing temperature rises, the film tends to be denser and obtains a lower surface roughness, a narrower optical-band gap and less oxygen-vacancy content. However, the μ-PCD test shows the 250 °C-annealed film obtains the least defects. And the PrIZO TFT annealed at 250 °C exhibited a desired performance with a saturation mobility (μsat) of 14.26 cm2·V−1·s−1, a subthreshold swing (SS) of 0.14 V·dec−1, an interface trap density (Dit) of 3.17 × 1011, an Ion/Ioff ratio of 1.83 × 108 and a threshold voltage (Vth) of −1.15 V. The flexible devices were prepared using the optimized parameters on the Polyimide (PI) substrate and subjected to static bending tests. After bending at a radius of 5 mm, the mobility of devices decreases slightly from 12.48 to 10.87 cm2·V−1·s−1, demonstrating the great potential of PrIZO for flexible displays.